Climate Change and Conflicting Future Visions - Larrabee, David A. (Zygon, 2018)
Dealing with the effects of climate change requires the consideration of multiple conflicting moral claims. The prioritization of these claims depends on the vision of a desired future, eschatology broadly defined. These visions, sometimes implicit rather than explicit, shape our decision making by influencing our sense of how things ought to be. The role of future visions in economics, technology, and preservation of nature are explored as secular eschatologies. Four aspects of such visions are especially relevant to climate change decisions: distributive justice, land use, the relationship among humans, and our relationship to the rest of nature. Effectively dealing with such wicked problems requires that we scrutinize our visions of how the future ought to be, both technically and morally. Finally, we must foster a dialogue between competing visions so that we can forge a path that strives for consent.